Experimental and numerical investigation of the photo-mechanical response of azobenzene filled soft elastomers, Part I: Experimental investigations - Mehnert, Markus; Moreno Mateos, Miguel Angel; Griwatz, Jan H.; Müsse, Silke; Wegner, Hermann A.; Steinmann, Paul (Extreme Mechanics Letters, 2024)
Photosensitive elastomers have the ability to undergo significant deformations upon the illumination by light of a specific wave length. Compared to other non-mechanical stimuli used in materials such as electro- or magneto-active polymers, light offers interesting advantages such as ultra high application speed and spatial precision. Moreover, as light powers and controls the movement of the material, the need for stiff wiring or external energy sources is eliminated. This becomes especially important in the design of miniature sized applications such as nano-scale robots. In the scope of the present work the conversion of photonic energy into a mechanical response originates from switching molecules embedded into a soft polymer matrix. Upon stimulation by UV-light, these molecules can switch from their stable trans - into a meta-stable cis-isomer, which induces a mechanical response on the macro scale. Depending on the experiment this can be visible as a deformation of the material or an increase in stiffness. This contribution presents the results of various mechanical and photo-mechanical experiments performed with the silicone Elastosil P 7670™ mixed with azobenzene molecules. These experiments are conducted in such a fashion that the obtained results are well suited for the identification of material parameters that arise from a photo-viscoelastic continuum modeling approach.<br
Keywords: Photo-sensitive materials; Soft elastomers; Photo-mechanics